THE IMPACT OF MUSIC LESSONS IN PRESCHOOL EDUCATION ON CHILDREN'S DEVELOPMENT AND THE FORMATION OF AESTHETIC TASTE THROUGH ARTISTIC ACTIVITIES (Scientific Conference on Multidisciplinary Studies, 2025)
This research explores the significance of music lessons in preschool education for fostering children’s overall development and shaping their aesthetic taste through artistic activities. Early childhood music education creates a stimulating environment that promotes cognitive, emotional, and social growth while encouraging creativity and an appreciation for the arts. Engaging in singing, playing instruments, rhythm exercises, and musical games helps children improve memory, attention, and auditory skills, as well as express emotions and cultivate social abilities such as cooperation and empathy. Additionally, exposure to musical experiences contributes to the development of aesthetic sensibilities, including the capacity to recognize harmony, rhythm, and beauty in artistic expressions. The study emphasizes the value of incorporating music-based activities into preschool programs to support comprehensive development, foster artistic creativity, and nurture early aesthetic awareness.